“A STUDY ON BUSINESS OPPORTUNITY IN WASTE RECYCLING AND UPCYCLING WITH REFERENCE TO UDUPI DISTRICT” - Mr. Kishor Krishna Marakala; Ms. Pooja (International Educational Journal of Science and Engineering, 2026)
The growing concerns of environmental degradation and resource scarcity have positioned waste recycling and upcycling as critical pathways for sustainable development. This study, titled “Business Opportunity in Waste Recycling and Upcycling with Reference to Udupi District”, investigates the potential for entrepreneurial ventures that transform waste into valuable resources while simultaneously addressing ecological challenges. The research emphasizes the increasing generation of municipal solid waste, plastic, paper, e-waste, and organic refuse in Udupi District, and explores how systematic recycling and innovative upcycling practices can be harnessed to create viable business models. The study adopts a descriptive and analytical approach, examining existing recycling initiatives, government policies, and community participation, while identifying gaps that can be leveraged by entrepreneurs. Special attention is given to opportunities in compost production, plastic reprocessing, paper and textile recycling, and creative upcycling for consumer markets. The findings reveal that Udupi District, with its expanding urbanization, educational institutions, and environmentally conscious population, offers fertile ground for green entrepreneurship. Furthermore, the study underscores the role of technology adoption, skill development, and public-private partnerships in strengthening the waste management ecosystem. It concludes that waste recycling and upcycling, when strategically integrated into local economic planning, can generate employment, foster innovation, and contribute to the realization of a circular economy. Thus, the district holds significant promise for sustainable business ventures that align economic growth with environmental stewardship.